Antidote to cannabinoid intoxication: the CB1 receptor inverse agonist, AM251, reverses hypothermic effects of the CB1 receptor agonist, CB‐13, in mice. (20th September 2017) - Pryce, Gareth; Baker, David
Abstract : Background and Purpose: Cannabis is a recreational drug leading to intoxication, following stimulation of cannabinoid CB1 receptors. However, more recently, herbs mixed with synthetic cannabinoids sometimes known as 'Spice' and 'Black Mamba' have been increasingly used, and their high CB1 receptor affinity has led not only to marked intoxication but also life‐threatening complications and an increasing number of deaths. Although many studies have indicated that prophylactic treatment with CB1 receptor antagonists can block cannabimimetic effects in animals and humans, the aim of this study was to determine whether CB1 receptor antagonism could reverse physical cannabimimetic effects. Experimental Approach: Cannabimimetic effects, measured by the hypothermic response following sedation and hypomotility, were induced by the synthetic CB1 receptor agonist CB‐13 (1‐naphthalenyl[4‐(pentyloxy)‐1‐naphthalenyl]methanone) in Biozzi Antibody High mice. The CB1 receptor antagonist/inverse agonist AM251 ( N ‐(piperidin‐1‐yl)‐5‐(4‐iodophenyl)‐1‐(2, 4‐dichlorophenyl)‐4‐methyl‐1 H ‐pyrazole‐3‐carboxamide) was administered 20 min after the injection of CB‐13 and its effects on the cannabimimetic responses were assessed. Key Results: In this study, the CNS‐related cannabimimetic effects, as measured by the hypothermic effect, induced by the CB1 receptor agonist were therapeutically treated and were rapidly reversed by the CB1 receptor antagonist/inverse agonist. There was also a subjective reversal of visually evident sedation. Conclusions and Implications: Cannabinoid receptor antagonists have been widely used and so may provide an acceptable single‐dose antidote to cannabinoid intoxication. This use may save human life, where the life‐threatening effects are mediated by cannabinoid receptors and not off‐target influences of the synthetic cannabinoids or non‐cannabinoids within the recreational drug mixture.